Variation of positive predictive values of fecal immunochemical tests by polygenic risk score in a large screening cohort - Niedermaier, Tobias; Balavarca, Yesilda; Gies, Anton; Weigl, Korbinian; Guo, Feng; Alwers, Elizabeth; Hoffmeister, Michael; Brenner, Hermann (Clinical and translational gastroenterology, 2022)
INTRODUCTION: - Prevalence of colorectal neoplasms varies by polygenic risk scores (PRS). We aimed to assess to what extent a PRS might be relevant for defining personalized cutoff values for fecal immunochemical tests (FITs) in colorectal cancer screening. - METHODS: - Among 5,306 participants of screening colonoscopy who provided a stool sample for a quantitative FIT (Ridascreen Hemoglobin or FOB Gold) before colonoscopy, a PRS was determined, based on the number of risk alleles in 140 single nucleotide polymorphisms. Subjects were classified into low, medium, and high genetic risk of colorectal neoplasms according to PRS tertiles. We calculated positive predictive values (PPVs) and numbers needed to scope (NNS) to detect 1 advanced neoplasm (AN) by the risk group, and cutoff variation needed to achieve comparable PPVs across risk groups in the samples tested with Ridascreen (N = 1,271) and FOB Gold (N = 4,035) independently, using cutoffs yielding 85%, 90%, or 95% specificity. - RESULTS: - Performance of both FITs was very similar within each PRS group. For a given cutoff, PPVs were consistently higher by 11%-15% units in the high-risk PRS group compared with the low-risk group (all P values < 0.05). Correspondingly, NNS to detect 1 advanced neoplasm varied from 2 (high PRS, high cutoff) to 5 (low PRS, low cutoff). Conversely, very different FIT cutoffs would be needed to ensure comparable PPVs across PRS groups. - DISCUSSION: - PPVs and NNS of FITs varied widely across people with high and low genetic risk score. Further research should evaluate the relevance of these differences for personalized colorectal cancer screening.
Gesehen am 11.05.2022